Comparison of NCAA D1 women`s basketball game day and previous practice training loads - Jean, K.; Mesquita, K. A.; Clark, D.; Sekiguchi, S. (International Journal of Exercise Science Conference Proceedings, 2025)
Game day training loads in NCAA Division I Women`s Basketball players differ significantly from practice loads, emphasizing the intense physical demands of competition. Analyzing these variations is crucial for optimizing training strategies, balancing workload, and enhancing recovery.